Embolisation of Prostatic Arteries as Treatment of Moderate to Severe Lower Urinary Symptoms (LUTS) Secondary to Benign Hyperplasia: Results of Short- and Mid-Term Follow-Up - Pisco, JM (2013)
OBJECTIVES: To evaluate the short- and medium-term results of prostatic arterial embolisation (PAE) for benign prostatic hyperplasia (BPH). METHODS: This was a prospective non-randomised study including 255 patients diagnosed with BPH and moderate to severe lower urinary tract symptoms after failure of medical treatment for at least 6 months. The patients underwent PAE between March 2009 and April 2012. Technical success is when selective prostatic arterial embolisation is completed in at least one pelvic side. Clinical success was defined as improving symptoms and quality of life. Evaluation was performed before PAE and at 1, 3, 6 and every 6 months thereafter with the International Prostate Symptom Score (IPSS), quality of life (QoL), International Index of Erectile Function (IIEF), uroflowmetry, prostatic specific antigen (PSA) and volume. Non-spherical polyvinyl alcohol particles were used. RESULTS: PAE was technically successful in 250 patients (97.9 %). Mean follow-up, in 238 patients, was 10 months (range 1-36). Cumulative rates of clinical success were 81.9 %, 80.7 %, 77.9 %, 75.2 %, 72.0 %, 72.0 %, 72.0 % and 72.0 % at 1, 3, 6, 12, 18, 24, 30 and 36 months, respectively. There was one major complication. CONCLUSIONS: PAE is a procedure with good results for BPH patients with moderate to severe LUTS after failure of medical therapy. KEY POINTS: • Prostatic artery embolisation offers minimally invasive therapy for benign prostatic hyperplasia. • Prostatic artery embolisation is a challenging procedure because of vascular anatomical variations. • PAE is a promising new technique that has shown good results.